Integrative Socio-Legal Model of Sexual Violence Prevention through Habonaron Do Bona - Nelvitia Purba; Mella Ismelina Farma Rahayu; Khomaini; Seguito Monteiro (International Journal of Law and Society, 2026)
Sexual violence against women remains a persistent socio-legal problem in Indonesia despite the enactment of Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS). This study aims to analyse the implementation of the UU TPKS in Simalungun Regency and examine the role of Habonaron Do Bona in strengthening victim-centred socio-legal protection within an integrative legal framework. This study employs a socio-legal research design combining normative juridical analysis of UU TPKS, particularly Articles 66–70 on victim rights, restitution, and recovery, with empirical qualitative data obtained through interviews, field observations, and document analysis involving law enforcement officers, customary leaders, legal practitioners, and victim support actors. The findings show weak implementation of UU TPKS at the local level. Restitution mechanisms under Articles 67–70 are rarely applied, resulting in minimal compensation for victims due to procedural barriers and limited law enforcement facilitation. Victim recovery rights under Article 66 are also not effectively implemented because psychosocial and medical services remain fragmented. Informal settlement practices persist, reducing access to formal justice. Patriarchal norms, stigma, and community pressure drive low reporting rates. Empirically, Habonaron Do Bona reflects values of truth and justice but is often interpreted to prioritise social harmony over victim protection. The study’s novelty lies in empirically repositioning local wisdom within an integrative socio-legal model that connects legal pluralism with state victim protection mechanisms. The findings imply the need to strengthen restitution enforcement, integrate recovery services, and develop culturally sensitive prevention strategies. The study is limited to one region and qualitative data, suggesting the need for comparative future research.